Validity of the problem-based learning model based on metacognitive oriented to improve critical thinking skills - Muhammad Habib Ramadhani; C Caswita; Een Yayah Haenilah (SAINTIS Publishing, 2022)
This study aims to develop a problem-based learning model based on metacognitive that is oriented towards improving students' critical thinking skills. This research is a Research Development. The research procedure used for research and development by Borg Gall. The development steps include: Research and Information Collection, Planning, Develop Preliminary of Product, validation by experts, Preliminary Testing, and Main Field Test. However, this research is limited to the step of validation by experts. The subjects of this research were 1 teacher and 2 lecturers. This research instrument are validation sheet for experts and a validation sheet for practitioners. The results of this research are (1) the design of a problem-based learning model based on metacognitive that is oriented towards improving critical thinking skills; (2) learning tools in the form of: Learning Implementation Plans and Student Worksheets in the topic “the three dimensional (3D) shape with flat surface ” of class VIII SMP even semester. The results of the expert and practitioner's validation analysis met the valid criteria. The model development design assessment score is 80%, Learning Implementation Plan score is 88%, and the Student Worksheet score is 88%. Overall, the product developed is suitable for use. Based on the assessment by experts, theoretically, product development can be used to improve students' critical thinking skills.